The Complexity of Microglial Interactions With Innate and Adaptive Immune Cells in Alzheimer’s Disease - Wyatt-Johnson, Season K.; Brutkiewicz, Randy R. (Frontiers in Aging Neuroscience, 2020)
In the naïve mouse brain, microglia are the most abundant immune cell; however, there is a complexity of other immune cells present including monocytes, neutrophils, and lymphocytic cells, such as natural killer (NK) cells, T cells, and B cells. In Alzheimer’s disease (AD), there is high inflammation, reactive microglia, leaky blood brain barrier, and the buildup of amyloid beta (Aβ) plaques which attract infiltrating peripheral immune cells that are interacting with the resident microglia. Limited studies have analyzed how these infiltrating immune cells contribute to the neuropathology of AD and even fewer have analyzed their interactions with the resident microglia. Understanding the complexity and dynamics of how these immune cells interact in AD will be important for identifying new and novel therapeutic targets. Thus, this review will focus on discussing our current understanding of how macrophages, neutrophils, NK cells, T cells, and B cells are altered in AD and what this means for the disorder, as well as how these cells are affected relative to the resident microglia.